APPLICATION OF POSITION-SENSITIVE ATOM PROBE TO THE STUDY OF THE MICROCHEMISTRY AND MORPHOLOGY OF QUANTUM WELL INTERFACES - Liddle, J; Norman, A; Cerezo, A; Grovenor, C (1989)
The morphology and microchemistry of interfaces in GaInAs/InP quantum well structures have been studied with extremely high resolution by the new technique of position sensitive atom probe microanalysis. This letter presents some preliminary results demonstrating the power of the technique in determining the structure and chemistry of individual interfaces in multilayer epitaxial semiconductor samples.